Inactivation of Indoor Environmental Allergy‑Related Substances by Ozonated Water In Vitro - Murakami, Yoshinobu; Tobi, Yukio; Emura, Kota; Baba, Kimiye; Taniguchi, Masahiko; Furukawa, Fukumi (Trends in Immunotherapy, 2025)
Allergic diseases are thought to be caused by a combination of acquired immune activation, excessive activation of innate immunity, and disruption of epithelial barrier function due to scratching, proteases, and more. The removal and inactivation of allergy-related substances in indoor environments are considered effective for reducing allergic disease symptoms. The typical allergens in Japan are Japanese cedar pollen and house dust mites (HDM), and together with bacteria and fungi, HDM are the main sources of proteases in indoor environments. We investigated the inactivating effects of ozonated water on these substances in vitro in terms of allergenicity, inflammation induction in epithelial and immune cell lines (i.e., HaCaT, A549, and RAW 264 cells), and protease activity. We observed that ozonated water inactivated the Japanese cedar pollen allergen Cry j1 and the HDM allergen Der f1, the innate immune activator lipoteichoic acid from the bacterium Staphylococcus aureus, and proteases from S. aureus, HDM, and the fungus Alternaria in an ozone concentration-dependent manner. In all experiments, ozonated water at 7.5 mg/L significantly inactivated allergy-related substances compared to the untreated group (p < 0.01). The comparison of the effects of ozonated water treatment and thermal treatment at 80 °C revealed that ozonated water treatment is superior to thermal treatment in terms of both effectiveness and reaction time. Together, our findings demonstrate that ozonated water can inactivate allergy-related substances in the indoor environment. The management of indoor environments using ozonated water can thus be expected to contribute to the alleviation of symptoms and suppression of allergic diseases.